Research progress of inflammatory cytokines in the diagnosis and treatment of amyotrophic lateral sclerosis - LI Xiao-guang, YANG Lu, LIU Xu-dong, JIA Xin-miao, CHENG Yan-fei, CUI Li-ying (Jichu yixue yu linchuang, 2022)
Amyotrophic lateral sclerosis (ALS) is a multifactor, multiple genes disease which involving a variety of mechanisms. Neuroinflammatory response is one of the mechanisms. Many inflammatory cytokines are involved. It may be used in clinic as biomarkers and therapeutic targets. Many proteins encoded by mutant genes can damage the function of immune system, lead to immune dysfunction and drive the inflammatory response of central nervous system and peripheral immune system. There are many kinds of inflammatory cytokines with great diversification in their levels which influenced by the stage, type and comorbidity of the disease, the results are not consistent at present, and there is no single inflammatory cytokine identified as a specific marker. Inflammatory cytokines have a certain prospect as therapeutic monitoring markers and targets.